Broadening the debate on creativity and dementia: A critical approach. (November 2019) - Bellass, Sue; Balmer, Andrew; May, Vanessa; Keady, John; Buse, Christina; Capstick, Andrea; Burke, Lucy; Bartlett, Ruth; Hodgson, James
In recent years there has been a growing interest in person-centred, 'living well' approaches to dementia, often taking the form of important efforts to engage people with dementia in a range of creative, arts-based interventions such as dance, drama, music, art and poetry. Such practices have been advanced as socially inclusive activities that help to affirm personhood and redress the biomedical focus on loss and deficit. However, in emphasizing more traditional forms of creativity associated with the arts, more mundane forms of creativity that emerge in everyday life have been overlooked, specifically with regard to how such creativity is used by people living with dementia and by their carers and family members as a way of negotiating changes in their everyday lives. In this paper, we propose a critical approach to understanding such forms of creativity in this context, comprised of six dimensions: everyday creativity; power relations; ways to operationalise creativity; sensory and affective experience; difference; and reciprocity. We point towards the potential of these dimensions to contribute to a reframing of debates around creativity and dementia.